First In Situ Observation of Sperm Release in Corynactis carnea (Anthozoa: Corallimorpharia) from Patagonia, Argentina - Bravo, Gonzalo (2023)
Jewel sea anemones constitute a relatively small group of solitary cnidarians, a sister group of scleractinian corals. In the southwest Atlantic Ocean off Argentina, two species of jewel sea anemones have been found: Corynactis carnea and Corallimorphus rigidus. Corynactis carnea is a common and abundant species in shallow water of northern Atlantic Patagonia, but reproductive data on this species is scarce; the species is known to reproduce asexually. During a SCUBA diving survey in an Atlantic rocky reefs (20 m depth) in Patagonia, we observed for the first time specimens of C. carnea releasing sperm, eight days after the full moon and during the summer season while spawning has been previously observed in at least three species of Corynactis, but all were recorded as occurring in winter.